Early rise in brain damage markers and high ICOS expression in CD4+ and CD8+ T cells during checkpoint inhibitor-induced encephalomyelitis. Issue 7 (2nd July 2021) - Bjursten, Sara; Pandita, Ankur; Zhao, Zhiyuan; Fröjd, Charlotta; Ny, Lars; Jensen, Christer; Ullerstam, Tobias; Jespersen, Henrik; Borén, Jan; Levin, Malin; Zetterberg, Henrik; Rudin, Anna; et al.
Abstract : We report a case of rapid eradication of melanoma brain metastases and simultaneous near-fatal encephalomyelitis following double immune checkpoint blockade. Brain damage marker S-100B and C reactive protein increased before symptoms or signs of encephalomyelitis and peaked when the patient fell into a coma. At that point, additional brain damage markers and peripheral T cell phenotype was analyzed. The analyses were repeated four times during the patient's recovery. Axonal damage marker neurofilament light polypeptide (NFL) and astrocytic damage marker glial fibrillar acidic protein (GFAP) were very high in blood and cerebrospinal fluid and gradually normalized after immunosuppression and intensive care. The costimulatory receptor inducible T cell costimulatory receptor (ICOS) was expressed on a high proportion of CD4+ and CD8+T cells as encephalomyelitis symptoms peaked and then gradually decreased in parallel with clinical improvement. Both single and double immune checkpoint inhibitor-treated melanoma patients with other serious immune-related adverse events (irAE) (n=9) also expressed ICOS on a significantly higher proportion of CD4+ and CD8+T cells compared with controls without irAE (n=12). In conclusion, our results suggest a potential role for ICOS on CD4+ and CD8+T cells in mediating encephalomyelitis and other serious irAE. In addition, brain damage markers in blood could facilitate early diagnosis of encephalitis.